Dynamic stability during level walking and obstacle crossing in children aged 2–5 years estimated by marker-less motion capture - Yoshimoto, Kohei; Mani, Hiroki; Hirose, Natsuki; Kurogi, Takaki; Aiko, Takumi; Shinya, Masahiro (Frontiers in Sports and Active Living, 2023)
In the present study, dynamic stability during level walking and obstacle crossing in typically developing children aged 2–5 years (n = 13) and healthy young adults (n = 19) was investigated. The participants were asked to walk along unobstructed and obstructed walkways. The height of the obstacle was set at 10% of the leg length. Gait motion was captured by three RGB cameras. 2D body landmarks were estimated using OpenPose, a marker-less motion capture algorithm, and converted to 3D using direct linear transformation (DLT). Dynamic stability was evaluated using the margin of stability (MoS) in the forward and lateral directions. All the participants successfully crossed the obstacles. Younger children crossed the obstacle more carefully to avoid falls, as evidenced by obviously decreased gait speed just before the obstacle in 2-year-olds and the increased in maximum toe height with younger age. There was no significant difference in the MoS at the instant of heel contact between children and adults during level walking and obstacle crossing in the forward direction, although children increased the step length of the lead leg to a greater extent than the adults to ensure base of support (BoS)-center of mass (CoM) distance. In the lateral direction, children exhibited a greater MoS than adults during level walking [children: 9.5%, adults: 6.5%, median, W = 39.000, p <.001, rank-biserial correlation = -0.684]; however, some children exhibited a smaller MoS during obstacle crossing [lead leg: -5.9–3.6% (min–max) for 4 children, 4.7–6.4% (95% confidence interval [CI]) for adults, p < 0.05; trail leg: 0.1–4.4% (min–max) for 4 children, 4.7–6.4% (95% CI) for adults, p < 0.05]]. These results indicate that in early childhood, locomotor adjustment needed to avoid contact with obstacles can be observed, whereas lateral dynamic stability is frangible.